2004
DOI: 10.1128/aac.48.11.4430-4434.2004
|View full text |Cite
|
Sign up to set email alerts
|

Activity of OPT-80, a Novel Macrocycle, Compared with Those of Eight Other Agents against Selected Anaerobic Species

Abstract: Clostridium difficile is a leading cause of antibiotic-associated diarrhea, especially in hospitals and long-term facilities (8,11,12). The organism accounts for about 20% of hospitalized patients who develop diarrhea after treatment with anti-infectives (and occasionally cytotoxic chemotherapeutic agents) and the majority of cases of antibiotic-associated colitis (3,7,10,17). The rising incidence of C. difficile-associated diarrhea has been attributed to the increasingly common prescription of broad-spectrum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
56
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(59 citation statements)
references
References 17 publications
2
56
1
Order By: Relevance
“…The narrow antimicrobial spectrum of activity of fidaxomicin has been well established by several studies; however, there are no data on the killing kinetics of the compound and its major metabolite (Ackermann et al, 2004;Credito & Appelbaum, 2004;Finegold et al, 2004). This study investigated the killing rate of both fidaxomicin and OP-1118 in comparison with vancomycin in wild-type hypervirulent strains, as well as in laboratory-derived strains with reduced susceptibility to fidaxomicin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The narrow antimicrobial spectrum of activity of fidaxomicin has been well established by several studies; however, there are no data on the killing kinetics of the compound and its major metabolite (Ackermann et al, 2004;Credito & Appelbaum, 2004;Finegold et al, 2004). This study investigated the killing rate of both fidaxomicin and OP-1118 in comparison with vancomycin in wild-type hypervirulent strains, as well as in laboratory-derived strains with reduced susceptibility to fidaxomicin.…”
Section: Introductionmentioning
confidence: 99%
“…Fidaxomicin (formerly OPT-80 and PAR-101) is a novel, narrow-spectrum antibiotic in development for the treatment of C. difficile infection (Ackermann et al, 2004;Credito & Appelbaum, 2004;Finegold et al, 2004). The putative target for fidaxomicin is the RNA polymerase (Talpaert et al, 1975).…”
Section: Introductionmentioning
confidence: 99%
“…The broad-spectrum antibacterial activities of metronidazole and vancomycin are thought to contribute to recurrence by preventing the regrowth of healthy intestinal flora (29)(30)(31)(32)(33). A newer treatment, fidaxomicin, has a narrower spectrum of activity than vancomycin or metronidazole (34)(35)(36) and causes less alteration to the intestinal flora of CDI patients (32,33). Consistent with this narrower spectrum of activity, multiple clinical trials have demonstrated a lower rate of CDI recurrence after treatment with fidaxomicin than after vancomycin or metronidazole treatment (37,38).…”
mentioning
confidence: 66%
“…The molecular structure of fidaxomicin is shown in Figure 1. In vitro, fidaxomicin is bacteriocidal against many species of Clostridia and all types of C. difficile compared with vancomycin, which is bacteriostatic [Ackermann et al 2004;Credito and Appelbaum, 2004;Finegold et al 2004;Karlowsky et al 2008;Hecht et al 2007]. In vitro, fidaxomicin kills organisms more rapidly with a prolonged postantibiotic effect (5.5-10 h) compared with vancomycin (0-1.5 h) Biedenbach et al 2010].…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…[Louie et al 2011]. The Minimum Inhibitory Concentration required to inhibit the growth of 90% of organisms (MIC 90 ) of fidaxomicin against C. difficile ranges between 0.0078 and 0.25 µg/ml [Ackermann et al 2004;Credito and Appelbaum, 2004;Finegold et al 2004]. Fidaxomicin is poorly active against gramnegative organisms, Bacteroides spp.…”
Section: Mechanism Of Actionmentioning
confidence: 99%